Substantiation of methodical approaches to the control of indoor radon concentration in existing public buildings with non-round-the-clock stay of people - A. S. Vasilyev; I. K. Romanovich; D. V. Kononenko; T. A. Kormanovskaya; K. A. Saprykin; T. A. Balabina (Радиационная гигиена)
According to the analysis of requests for methodological assistance to the Saint-Petersburg Research In stitute of Radiation Hygiene after Professor P. V. Ramzaev, measurements of radon concentration (or radon EEC) in existing operated public buildings (primarily children institutions) in the framework of surveillance actions in the regions of the Russian Federation, as a rule, are taken according to Guidelines MU 2.6.1.2838-11, intended for radiation control of public buildings only when they are put into operation after construction, major repairs or reconstruction, due to the absence of special guidelines. Compliance with the requirements of paragraph 6.5 of MU 2.6.1.2838-11 means that the building and premises are in a state that is not equal to their normal operation mode. Registration of high values of indoor radon concentration in this case leads to management decisions, including administrative suspension o f activities for up to ninety days, i.e. the closure of individual premises or even the entire building of a children institution. The consequences of making such decisions may include an increase in social tension in society and provoking radiophobia among the population. The paper presents specific recommendations for the radon survey for existing operated public buildings with non-round-the-clock stay of people, which are based on the results of the analysis of the experience of practical application of various methods of measuring indoor radon concentrations in such buildings in order to assess average radon concentration during working hours in the normal operation mode. The proposed approach can be further used as the basis for developing special guidelines for radiation control of existing operated public buildings with non-round-the-clock stay of people.